ON THE EFFECTIVE CONTRACT IN HIGHER SCHOOL OF RUSSIA - Vasily S. Senashenko; Vladimir G. Khalin (Высшее образование в России)
The article discusses the problems and consequences of introducing in national universities effective contract management. The possibilities of using it as a tool for improving the system of remuneration, to motivate teachers to research activities and «harmonization» of the relationship between teachers and administrators. Special attention is given to the description of university management system and the characteristics of universities’ interaction with the academic personnel in terms of improving quality and competitiveness of the faculty in the world market of educational services. The article formulates a set of proposals improving the systems of remuneration and academic contracts for the faculty members at the universities of Russia.